Eksplorasi Hambatan Guru Dalam Mengimplementasikan Pembelajaran Bahasa Indonesia Berbasis Teks Deskripsi - Nur Hikmah; Rasyikh Aisyah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to explore the various obstacles faced by teachers in implementing descriptive text-based Indonesian language learning in junior high schools. Using qualitative descriptive methods, data were collected through interviews, classroom observations, and documentation analysis involving Indonesian language teachers. The research findings indicate that teachers face several challenges, including limited understanding of the concepts and structure of descriptive texts, difficulties in developing creative and student-centered learning strategies, inadequate availability of learning resources, and low student motivation and vocabulary mastery. Furthermore, time constraints and heavy administrative tasks reduce teachers' opportunities to design effective descriptive text learning activities. This study highlights the need for continuous professional development, the provision of adequate teaching materials, and supportive school policies to optimize the implementation of descriptive text-based learning. These findings are expected to contribute to improving the quality of Indonesian language learning, particularly in improving students' descriptive writing skills.